The Study of Generic Patterns of Mission and Vision Statements of the Universities - Naveed Nawaz Ahmad (IDEA PUBLISHERS, 2020)
Due to the significance of mission and vision statements (MS and VS) in academia across the world, this study aims at analysing generic patterns of MS and VS of universities from four different countries:  two belonging to the native users of English language (UK and US) and the other two from non-native contexts (Pakistan and India). The purpose of the study is to investigate the rhetorical patterns in vision and mission statements to uncover structures used to establish universities’ global outreach and competitiveness in research and teaching. The data was collected from university websites and analysed through genre-based approach of Move Analysis introduced by Swales (2004) and applied on promotional genres by Bhatia (2004). The overall rhetorical structures of vision and Mission statements comprised of three moves with each move realized through further steps. The findings revealed that text of MS and VS provides the information about the university with an intended purpose of attracting the students by declaring the values, aims, obligations and strategic plans alongside establishing the aspects of global outreach and status in education and research as well as enriching the society and facilitating the individuals with the provision of best resources.